2013
DOI: 10.1124/dmd.112.050005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of the Structural Components of Adenosine Diphosphate-Encapsulated Liposomes Coated with Fibrinogenγ-Chain Dodecapeptide as a Synthetic Platelet Substitute

Abstract: Fibrinogen g-chain (dodecapeptide HHLGGAKQAGDV, H12)-coated, ADP-encapsulated liposomes [H12-(ADP)-liposomes] were developed as a synthetic platelet alternative that specifically accumulates at bleeding sites as the result of interactions with activated platelets via glycoprotein IIb/IIIa and augments platelet aggregation by releasing ADP. The aim of this study is to characterize the pharmacokinetic properties of H12-(ADP)-liposomes and structural components in rats, and to predict the blood retention of H12-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…(b) The hepatic distribution of 14 C and 3 H radioactivity at 2 h after the first injection (closed bar) or the second injection (open bar) of 3 H , 14 C radiolabeled H 12‐( ADP )‐liposome at a dose of 10 mg lipid/kg to healthy rats. The data for the first injection were cited from our previously reported paper . Each point represents the mean ± SD ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(b) The hepatic distribution of 14 C and 3 H radioactivity at 2 h after the first injection (closed bar) or the second injection (open bar) of 3 H , 14 C radiolabeled H 12‐( ADP )‐liposome at a dose of 10 mg lipid/kg to healthy rats. The data for the first injection were cited from our previously reported paper . Each point represents the mean ± SD ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…14 C, 3 H double‐labeled H12‐(ADP)‐liposomes were prepared as previously reported . The diameter and zeta‐potential of the 14 C‐labeled H12‐(ADP)‐liposomes used in this study were in the range of 250 ± 50 nm and −10 ± 0.9 mV, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5‐Dihexadecyl‐ N ‐succinyl‐ l ‐glutamate (DHSG) and H12‐PEG‐Glu2C18 were synthesized as reported previously . 14 C‐, 3 H‐abeled H12‐(ADP)‐liposomes were prepared, as described in a previous report . The diameter and zeta potential of the H12‐(ADP)‐liposomes used in this study were in the range of 250 ± 50 nm and −10 ± 0.9 mV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, previous in vitro and in vivo studies clearly showed that the modification of H12‐(ADP)‐liposomes such as H12 and encapsulation with ADP enables them to specifically interact with the glycoproteins IIb/IIIa on activated PLT and stimulate PLT aggregation. Furthermore, a pharmacokinetic study of H12‐(ADP)‐liposomes in healthy animals showed that they have an adequate circulation time in the blood to permit them to function as a PLT substitute and that they have acceptable biodegradable properties . Taken together with these characteristics of H12‐(ADP)‐liposomes in preclinical trials, H12‐(ADP)‐liposomes are promising candidates for use as a PLT substitute in clinical applications.…”
Section: Introductionmentioning
confidence: 99%